Nickel in soil and maize plants grown on an oxisol treated over a long time with sewage sludge - Rodrigues Nogueira, Thiago Assis; de Melo, Wanderley Jose [UNESP]; Oliveira, Leyser Rodrigues [UNESP]; Fonseca, Ivana Machado [UNESP]; Peruca de Melo, Gabriel Mauricio [UNESP]; Marcussi, Silvio Aparecido [UNESP]; Marques, Marcos Omir [UNESP] (Science Reviews 2000 Ltd, 2009)
The major limitation for the use of sewage sludge in agriculture is the risk of soil contamination with heavy metals, and their possible transference to man via the food chain. The objective of this study was to evaluate the content of nickel (Ni) in soil by the two methods of digestion (HNO(3)+H(2)O(2)+HCl and HClO(4)+HF), and in different parts of maize plants grown on a tropical soil classified as Typic Eutrorthox, that had been treated with sewage sludge for nine consecutive years, and the effects on dry matter and grain production. The experiment was carried out under field conditions in Jaboticabal-SP, using a randomized block design with four treatments and five replicates. Treatments consisted of: 0.0 (control, mineral fertilization), 45.0, 90.0 and 127.5 t ha(-1) sewage sludge (dry basis), accumulated during nine years. Sewage sludge was manually applied to the soil and incorporated at 0.1 m depth before sowing the maize. Soil Ni evaluated by Jackson's method was 76.8% higher than evaluated by the United States Environmental Protection Agency method that digests the samples by heating with concentrated HNO(3), H(2)O(2) and HCl. Sewage sludge rates did not affect Ni content in the soil. Ni was accumulated in leaf and stem but was not detected in grain. Sewage sludge and mineral fertilization applied to soil for a long time caused similar effects on dry matter and grain production.
Keywords: Zea mays L.; biosolids; Heavy metal; Soil pollution; urban residues; Mineral nutrition